Political Ideologies : An Introduction - Heywood, Andrew (Macmillan, 1992)
Ideology has had a strange history, it is inseparable from the political experience of the modern world, yet few major theorists of politics have a good word for it. Figures as diverse as Karl Marx,Michael Oakeshoot and Talcott Parsons all condemned it, for different reasons.